Cool runnings - Steel, Dawn.; Turteltaub, John.; Siefert, Lynne; Swerdlow, Tommy; Goldberg, Michael; Walt Disney Pictures ([Burbank, Calif.] Distributed by Buena Vista Pictures, Int'l., 1993)
Based on a true story, this is the comedic saga of four Jamaican athletes and their coach who compete as bobsled racers at the Calgary Winter Olympics with few resources and virtually no clue about winter sports. With pride, determination, and dignity, the bobsledders make their impossible dreams come true.
VHS.
Based on the true story of the 1988 Jamaican Olympic bobsled team.
Executive producers, Christopher Meledondri, Susan R. Landau ; story by Lynne Siefert and Michael Ritchie.
Leon, Doug E. Doug, Rawle D. Lewis, Malik Yoba, Raymond J. Barry, John Candy.
Keywords: Bobsledding; Winter Olympics; Comedy